Examination of condition of rolling bearings - Tóth, Dániel (Design of Machines and Structures, 2024)
Bearings operating properties impact the function of the whole machine therefore their investigation is an important topic. Early detection of failure of bearings allows for the replacement of them during planned maintenance, thus avoiding sudden downtime or unexpected accidents. There are several methods for monitoring the operating conditions of bearings, which help determine the residual lifetime of the bearings. This paper focuses on a test procedure which can be used to determine the condition of rolling element bearings.